Adverse Events and Unsuccessful Intubation Attempts Are Frequent During Neonatal Nasotracheal Intubations - Tippmann, Susanne; Haan, Martin; Winter, Julia; Mühler, Ann-Kathrin; Schmitz, Katharina; Schönfeld, Mascha; Brado, Luise; Mahmoudpour, Seyed Hamidreza; Mildenberger, Eva; Kidszun, André (Frontiers in Pediatrics, 2021)
Background: Intubation of neonates is difficult and hazardous. Factors associated with procedure-related adverse events and unsuccessful intubation attempts are insufficiently evaluated, especially during neonatal nasotracheal intubations. Objective: Aim of this study was to characterize the nasotracheal intubation approach and analyze factors associated with tracheal intubation–associated events (TIAEs) and unsuccessful intubation attempts. Methods: This was a prospective, single-site, observational study from May 2017 to November 2019, performed at a tertiary care neonatal intensive care unit in a German academic teaching hospital. All endotracheal intubation encounters (IEs) performed by the neonatal team were recorded. Results: 258 consecutive IEs in 197 patients were analyzed. TIAEs occurred in 57.4% of IEs. Intubation inexperience (<10 IEs) (OR=2.15; 95% CI, 1.257-3.685) and equipment problems (OR=3.43; 95% CI, 1.12-10.52) were predictive of TIAEs. Intubation at first attempt (OR=0.10; 95% CI, 0.06-0.19) and videolaryngoscopy (OR=0.47; 96% CI, 0.25-0.860) were predictive of IEs without TIAEs. Orotracheal intubation was performed in 5/258 (1.9%) IEs. Intubations due to unplanned extubations were rare (1.6% of IEs). The first intubation attempt was commonly done by pediatric residents (67.8%). Overall, a median of two attempts (39.4% at first attempt; 39.5% with > 2 attempts) were performed until successful intubation. Restricted laryngoscopic view (OR=3.07; 95% CI, 2.08-4.53; Cormack-Lehane grade 2 vs. grade 1), intubation by pediatric residents when compared to neonatologists (OR=1.74; 95% CI, 1.265-2.41) and less experienced neonatal nurses (OR=1.60; 95% CI, 1.04-2.46) were associated with unsuccessful intubation attempts. Conclusions: In our unit, TIAEs and unsuccessful intubation attempts occurred frequently during neonatal nasotracheal intubations. Quality improvement und further research should focus on interprofessional education and training, equipment problems and videolaryngoscopy.